(untitled) (International Seven Journal of Health Research, 2024)
The adenomatoid odontogenic tumor (AOT) is an uncommon, benign neoplasm of odontogenic epithelial origin, believed to have originated from two remnants of the dental lamina or enamel organ, representing 2-7% of all odontogenic tumors. Clinically, they are slow growing, asymptomatic and rarely exceed 3.0 cm in diameter. TOA presented three different clinicopathological variants without relevant clinical and radiographic differences: intraosseous follicular (associated with dental impaction, generally comprising 70% of the two cases); extra-follicular intraosseous (present between erupted teeth, representing 25% of the two cases); and peripheral (extra-osseous, 5% two cases). The aim of this paper is to report a case of a large and aggressive adenomatoid odontogenic tumor. Patient, male, 13 years old, undergoing direct increase in maxillary volume with evolution of 01 month. Upon physical examination, an increase in volume in the middle third of the face was observed, directly causing facial asymmetry. normal appearance, absence of unit, tooth 13, stable dental occlusion, poor mouth opening, poor oral hygiene. On imaging (face tomography) there was a hypodense image in the maxillary region directly, osteolytic, well circumscribed, with a radiopaque halo, causing expansion of the cortical bones without breaking them, associated with the impacted and included dental unit 13. Enucleation and complete healing of the lesion and associated extraction of unit 13 were performed, with a lesion presenting a fibrous capsule in the non-transoperative period. The patient is being followed up by a team, weeks of recurrence at the moment. In this way, a rapid and aggressive evolution appears, being clinically perceptible and confused with the behavior of an amelolastoma, however, the histopathological diagnosis of TOA was confirmed, although the lesion responded to a conservative surgical technique through enucleation and dressing, presenting a excellent result.